Respuesta :

Answer:

No solution

Step-by-step explanation:

-3x + 3y = 4

-x + y = 3

Solve the equation for x:

Move the variable to the right side and change its sign

-x + y = 3

-x = 3 - y

Change the signs on both sides of the equation

-x = 3 - y

x = -3 + y

Substitute the given value of x into the equation -3x + 3y = 4

-3x + 3y = 4

x = -3 + y

-3(-3+y)+3y=4

Solve the equation for y

-3(-3+y)+3y=4

y = 0

There is no solution for y.

And since there's no solution for y, the system has no solution.

ACCESS MORE